Study on semi-bionic extraction of Astragalus polysaccharide and its anti-aging activity in vivo - Yan, Xinlei; Miao, Jing; Zhang, Bao; Liu, Huan; Ma, Huifang; Sun, Yufei; Liu, Pufang; Zhang, Xiujuan; Wang, Ruigang; Kan, Juntao; Yang, Feiyun; Wu, Qiming (Frontiers in Nutrition, 2023)
Astragalus membranaceus (A. membranaceus) is a homologous plant with high medicinal and edible value. Therefore, the extraction methods of Astragalus polysaccharide (APS) have attracted the attention of many research groups, but the yield of active components is still not high. The aim of this study was to extract APS by a semi-biomimetic method, optimize the extraction process, and evaluate the anti-ageing activities of APS in vivo. The results showed that the APS yield was 18.23% when extracted by the semi-biomimetic method. Anti-ageing evaluation in rats showed that APS extracted by this method significantly decreased the malondialdehyde (MDA) content and increased superoxide dismutase (SOD) activity to cope with D-galactose-induced ageing. Serum metabonomic analysis indicated that a total of 48 potential biomarkers showed significant differences, mainly involving 5 metabolic pathways. These altered metabolic pathways were mainly related to energy metabolism, amino acid metabolism, and lipid metabolism. These results indicated that the semi-biomimetic method can effectively improve the yield of APS, and the extracted APS exhibited anti-ageing activity in rats. Our study provided a novel and effective method to extract APS and indicated that APS can be used as functional food and natural medicine to delay ageing and prevent its complications.